Perancangan Aplikasi Penjadwalan Perbaikan Elevator Dan Escalator Berbasis Web (CV. Kebalen Teknik Mandiri) - Subhan, Ahmad; Junaedi, Ifan; Sianipar, Anton Zulkarnain (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Technological developments are growing rapidly, making it easier for everyone. Technology has developed and produced internet-based information technology, in this concept the business world has also penetrated the world of technology in various fields including the service sector. However, in one company there are still those who schedule elevator and escalator repairs manually using the elevator and escalator repair scheduling form sheet. This manual system can sometimes cause several problems. In order to deal with teirseibuit problems, the proposed system will address teirseibuit problems in a comprehensive manner. The proposed system will simplify the process of scheduling repairs for elevators and escalators by utilizing web technology, as well as increasing time efficiency and constraints on damaged elevator and escalator repair schedule forms. The method used is to use the stages of the RAD (Rapid Application Development or Rapid Prototyping) method, which is a process model for balancing software devices which is classified as an incremental (multilevel) technique. The results of feature testing using the Black Box Testing method show that the system has been validated and meets the desired needs.